2020
DOI: 10.1111/hdi.12859
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of COVID‐19 in a patient on maintenance dialysis

Abstract: Coronavirus infectious disease (COVID-19) is a novel respiratory infection highly associated with severe complications in elderly subjects affected by cardiovascular disease. Patients on maintenance dialysis are exceptionally vulnerable because most of them are old and have multiple comorbidities. We report the complex clinical course of SARS-CoV-2 infection in a patient on maintenance dialysis who presented with fever and lung edema. After 41 days from the primary infection, the clinically recovered patient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…On average shedding of viral particles lasted 15.1–29 days in infected patients on HD [ 135 , 139 ]. Two studies reported that HD patients tested positive for SARS-CoV-2 RNA on repeated testing despite being negative on two prior consecutive nasopharyngeal swabs [ 138 , 140 ]. Prolonged viral RNA shedding has been reported until 79 days in an adult HD patient [ 140 ] and 28 days in a pediatric patient [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On average shedding of viral particles lasted 15.1–29 days in infected patients on HD [ 135 , 139 ]. Two studies reported that HD patients tested positive for SARS-CoV-2 RNA on repeated testing despite being negative on two prior consecutive nasopharyngeal swabs [ 138 , 140 ]. Prolonged viral RNA shedding has been reported until 79 days in an adult HD patient [ 140 ] and 28 days in a pediatric patient [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported that HD patients tested positive for SARS-CoV-2 RNA on repeated testing despite being negative on two prior consecutive nasopharyngeal swabs [ 138 , 140 ]. Prolonged viral RNA shedding has been reported until 79 days in an adult HD patient [ 140 ] and 28 days in a pediatric patient [ 141 ]. Only one anecdotal case of reinfection has been reported in a dialysis patient [ 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…On average, SARS‐CoV‐2 RNA shedding was measured for 44.6 ± 26.1 days; in one patient viral genetic material was detected for 74 days from the diagnosis of COVID‐19 and 79 from symptoms onset. 6 After the clearance of the virus, no cases of COVID‐19 reinfection were documented in these patients. As detailed in Table 1 , anti‐spike IgG antibodies (Ab) were measured in the serum of these three survivors after 1 year (range, 366–374 days) from the diagnosis of the SARS‐CoV‐2 infection.…”
Section: Resultsmentioning
confidence: 89%
“…After discharge, this group of patients continued to receive appropriate dialysis therapy in a separated room until the detection of two negative nasopharyngeal swabs for SARS‐CoV‐2. On average, SARS‐CoV‐2 RNA shedding was measured for 44.6 ± 26.1 days; in one patient viral genetic material was detected for 74 days from the diagnosis of COVID‐19 and 79 from symptoms onset 6 . After the clearance of the virus, no cases of COVID‐19 reinfection were documented in these patients.…”
Section: Resultsmentioning
confidence: 92%
“…“Long-hauler” clinics caring for and studying these patients will hopefully shed light on their pathophysiology. 7 …”
Section: Other Unresolved Problemsmentioning
confidence: 99%